2021
DOI: 10.1111/1471-0528.16966
|View full text |Cite
|
Sign up to set email alerts
|

Leaning towards Cytomegalovirus serological screening in pregnancy to prevent congenital infection: a cost‐effectiveness perspective

Abstract: Objective To assess the cost-effectiveness of prenatal detection of congenital cytomegalovirus (cCMV) following maternal primary infection in the first trimester within standard pregnancy followup or involving population-based screening (serological testing at 7 and 12 weeks of gestation), with or without secondary prevention (valaciclovir) in maternal CMV primary infection.Design Cost-effectiveness study from the perspective of the French national health insurance system.Setting Cost-effectiveness based on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
8
1
Order By: Relevance
“…A French study assessed the cost-effectiveness of prenatal detection of congenital cytomegalovirus following maternal primary infection during the first trimester within standard pregnancy follow-up or involving population-based screening (serological testing at 7 and 12 weeks of gestation). CMV serological screening followed by valaciclovir prevention might prevent 58% to 71% of severe congenital CMV cases for a cost of EUR 38 per pregnancy [112]. In this study, the cost of postnatal sequelae and care for these children was not considered.…”
Section: Diagnosis Of Maternal Infection and Screening Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A French study assessed the cost-effectiveness of prenatal detection of congenital cytomegalovirus following maternal primary infection during the first trimester within standard pregnancy follow-up or involving population-based screening (serological testing at 7 and 12 weeks of gestation). CMV serological screening followed by valaciclovir prevention might prevent 58% to 71% of severe congenital CMV cases for a cost of EUR 38 per pregnancy [112]. In this study, the cost of postnatal sequelae and care for these children was not considered.…”
Section: Diagnosis Of Maternal Infection and Screening Strategiesmentioning
confidence: 99%
“…Secondary prevention aims to avoid or reduce the risk of maternal-fetal transmission in case of proven CMV seroconversion in the mother [110]. The literature on secondary prevention of cCMV focuses on two complementary topics: maternal serological screening [111,112] and prophylactic therapies, including administration of hyperimmune globulin [24,113,114] or antiviral therapy [115]. Currently, practices regarding the application of these methods are site-specific as the effectiveness of these methods is still considered controversial [116].…”
Section: Secondary Prevention: To Reduce the Risk Of Maternal-fetal T...mentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the model's external validity by comparing external data from the literature 19,29,34 with the results for Strategy S1 (no systematic screening) in our model. The model results were close to the external data (Table S3).…”
Section: Model Validitymentioning
confidence: 99%
“…Several studies have shown that most pregnant women know little about CMV infection [ 23 ]. Although the role of CMV screening during pregnancy has been discussed over the last decade [ 24 , 25 ], CMV is the least known in pregnant women compared to other congenital infections or diseases [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%